Gabapentin and Amitriptilin Treatment toward Living Quality of Post Ischemic Stroke Patients with Neurophaty Pain - Pinasti Utami; Zulies Ikawati; Setyaningsih Setyaningsih (Intelektual Pustaka Media Utama, 2015)
Stroke becomes a significant problem for developing countries. In Indonesia the data show its incidences 234 per 100.000 people, and around 2 - 8 % stroke patients experiencing cerebrovascular session will get neurophaty pain. It happens because of sensoric deviation after stroke, so the brain does not completely send information to the body correctly. Patients experiencing neurophaty pain are able to face decreasing living quality as the effect of long term painful disturbance. Therefore, it is important to maintain the patients’ living quality. The aim of the study is to investigate the comparison of using gabapentin and amitriptilin toward living quality of ischemic stroke patients with neurophaty pain in the hospitals in Jogja. The method used in this study was quasi experimental with consequtive sampling. The study was conducted on 22nd of April-31st of Juli 2013 by involving 23 patients in gabapentin group and 18 patientsin amitriptilin group that would be evaluated during 1 month. Living quality was assessed by Brief Pain Inventory (BPI) in week 0 and week 4. The result of the study showed that the use of gabapentin and amitriptilin in 4 weeks showed the increase of living quality represented by decreasing the score based on BPI questioner 1.67±0.78 and 1.37±0.80 with p-value>0.05 meaning that there was no significant difference. It can be concluded the comparison of using gabapentin and amitriptilin in post ischemic stroke patient with neuropathy pain not significantly increase the quality of in the hospitals in Jogja.